P53 and Expression of Immunological Markers May Identify Early Stage Thyroid Tumors - Marjory Alana Marcello; Elaine Cristina Morari; Lucas Leite Cunha; Aline Carolina De Nadai Silva; Dirce Maria Carraro; André Lopes Carvalho; Fernando Augusto Soares; José Vassallo; Laura Sterian Ward (Clinical and Developmental Immunology)
Background. Besides its major role in cell proliferation, DNA repair, and apoptosis, functional p53 protein is involved in the induction of antitumor cytotoxic-T-cell activity against carcinoma cells. We aimed to investigate p53 and immune cell markers utility as diagnostic and prognostic markers of differentiated thyroid cancer (DTC). Methods. ACIS-III system was used to evaluate p53 and immune cell markers including tumor-associated macrophages (TAM); CD68 and tumor-infiltrating lymphocytes (TIL) subsets such as CD3, CD4, CD8, and CD20 in 206 thyroid carcinomas, 105 benign nodules, and 18 normal tissues. Also, TP53 was sequenced in 78 out of 164 patients with papillary thyroid carcinoma. Results. P53 expression was observed more frequently in malignant than in benign lesions (P<0.0001) and helped discriminate follicular patterned lesions. In addition, p53 was more frequent in smaller (P=0.0015), unique tumors (P=0.0286), with thyroiditis (P=0.0486) and without metastasis at diagnosis (P=0.0201). TAM was more frequent in P53 negative tumors (P=0.002). Infiltration of CD8+ TIL was found in 61.7% of P53 positive and 25.6% of P53 negative DTC (P<0.001). Conclusions. We suggest that p53 and CD8+ TIL immune profile analysis might be useful in DTC.